Imaging nanometer-sized α-synuclein aggregates by superresolution fluorescence localization microscopy - Roberti, Maria Julia (2012)
The morphological features of alpha-synuclein (AS) amyloid aggregation in vitro and in cells were elucidated at the nanoscale by far-field subdiffraction fluorescence localization microscopy. Labeling AS with rhodamine spiroamide probes allowed us to image AS fibrillar structures by fluorescence stochastic nanoscopy with an enhanced resolution at least 10-fold higher than that achieved with conventional, diffraction-limited techniques. The implementation of dual-color detection, combined with atomic force microscopy, revealed the propagation of individual fibrils in vitro. In cells, labeled protein appeared as amyloid aggregates of spheroidal morphology and subdiffraction sizes compatible with in vitro supramolecular intermediates perceived independently by atomic force microscopy and cryo-electron tomography. We estimated the number of monomeric protein units present in these minute structures. This approach is ideally suited for the investigation of the molecular mechanisms of amyloid formation both in vitro and in the cellular milieu.